Kinetics of B-lymphocytes stimulation by pokeweed Pa-1 mitogen and bacterial lipopolysaccharide. - Yokoyama, K (1979)
The presence of two subpopulations in mouse B lymphocytes responding to pokeweed Pa-1 mitogen or bacterial lipopolysaccharide (LPS) in terms of DNA synthesis was demonstrated. The analysis of surface markers of these two subpopulations revealed that one of the subpopulations carried the complement receptor (CR+) and the other lacked the complement receptor (CR-). The kinetics of stimulation by Pa-1 and LPS differed between these two subpopulations. CR+ -B cells exhibited the first peak of DNA synthesis 27 h after the addition of the mitogen, whereas CR- -B cells showed the first maximal response after 39 h. When the responses of CR+ -B cells 27 h and of CR- -B cells 39 h after various pulsed exposures to the mitogen were compared with those after continuous exposures to the mitogen, two successive 3 h exposures (0-3 and 12-15 h for CR+ -B cells; 0-3 and 21-24 h for CR- -B cells) yielded the same level of response as continuous exposure for 27 h (CR+ -B cells) or 39 h (CR- -B cells). These results indicate that both B-cell subpopulations require two signals for maximal stimulation.